(untitled) (translation. a transdisciplinary journal, 2021)
The world, as we know it, does not exist in an undivided state-the world is always a combination of marked and unmarked parts. Even if an observer attempts to observe the world in its entirety, the world will inevitably be divided into the observed and the observer. In other words, the world should be presented as ever-crossed, that is, containing a cross.